Diagnostic criteria for ductal adenocarcinoma of the prostate: interobserver variability among 20 expert uropathologists. Issue 2 (3rd April 2014) - Seipel, Amanda H; Delahunt, Brett; Samaratunga, Hemamali; Amin, Mahul; Barton, Joel; Berney, Daniel M; Billis, Athanase; Cheng, Liang; Comperat, Eva; Evans, Andrew; Fine, Samson W; Grignon, David; et al.
<x xml:space="preserve">Abstract</x> Aims Ductal adenocarcinoma of the prostate (DAC) is clinically important, because its behaviour may differ from that of acinar adenocarcinoma. Our aims were to investigate the interobserver variability of this diagnosis among experts in uropathology and to define diagnostic criteria. Methods and results Photomicrographs of 21 carcinomas with ductal features were distributed among 20 genitourinary pathologists from eight countries. DAC was diagnosed by 18 observers (mean 13.2 cases, range 6–19). In 11 (52%) cases, a 2/3 consensus was reached for a diagnosis of DAC, and in five (24%) there was consensus against. In DAC, the respondents reported papillary architecture (86%), stratification of nuclei (82%), high‐grade nuclear features (54%), tall columnar epithelium (53%), elongated nuclei (52%), cribriform architecture (40%), and necrosis (7%). The most important diagnostic feature reported for DAC was papillary architecture (59%), whereas nuclear and cellular features were considered to be most important in only 2–11% of cases. The most common differential diagnoses were intraductal prostate cancer (52%), high‐grade PIN (37%), and acinar adenocarcinoma (17%). The most common reason for not diagnosing DAC was lack of typical architecture (33%). Conclusions Papillary architecture was the most useful diagnostic feature of DAC, and nuclear and cellular features were considered to be less important.